PENGARUH OWNERSHIP STRUCTURE TERHADAP EARNINGS QUALITY DENGAN VOLUNTARY DISCLOSURE IN CORPORATE GOVERNANCE SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN TAHUN 2011-2016) - Inriani Yoseph; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the direct influence of ownership structure on voluntary disclosure in corporate governance and earnings quality. In addition, this study also aimed to examine the indirect influence of the ownership structure on earnings quality by using voluntary disclosure in corporate governance as a mediating variable. This study used firm size as control variable. The sample consisted of 39 mining companies listed in Indonesia Stock Exchange during the period of 2011- 2016. The data was collected from annual reports, then analyzed by using WarpPLS software version 5.0.The result revealed that there was no significant influence of ownership structure and firm size on earnings quality, but positive influence of ownership structure and firm size on voluntary disclosure in corporate governance, and positive influence of voluntary disclosure in corporate governance on earnings quality. Furthermore, this study also found that voluntary disclosure in corporate governance was able to mediate the influence of ownership structure on earnings quality.